The Effect of Inflation, Interest Rates, And Exchange Rates On Stock Prices In State-Owned Banking Companies Listed On The Indonesian Stock Exchange For The Period 2020-2024 - Tarisa Ashilah Aswin; Yanna Eka Pratiwi; Siwidyah Desi Lastianti; Ida Budiart (Journal of Economy, Accounting and Management Science (JEAMS), 2026)
This study examines the impact of macroeconomic variables—namely inflation, interest rates, and exchange rates—on the stock prices of state-owned banks (BUMN) listed on the Indonesia Stock Exchange during 2020–2024. Using secondary data from Bank Indonesia and IDX, the sample was selected through purposive sampling of banks consistently reporting monthly stock prices. Multiple linear regression was applied to assess simultaneous and partial effects. The results show that interest rates and exchange rates significantly and negatively influence stock prices, while inflation has no significant impact. These findings align with previous studies suggesting that exchange rate volatility and rising interest rates reduce the attractiveness of banking stocks. The study provides insights for investors, managers, and policymakers in designing investment strategies and economic policies, particularly in responding to post-pandemic economic challenges.